New sol-gel hybrid polydimethylsiloxane-glucosamine as stir bar sorptive extraction sorbent - Hazwanee Osman, 1987-; Wan Aini Wan Ibrahim, supervisor; Fakulti Sains (2009)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2009